Radiological features of dengue fever in cases and control - Bajpai, Gautam; Verma, R. K. (International Journal of Advances in Medicine, 2022)
Background: Dengue (pronounced DENgee) fever is a painful, debilitating mosquito-borne disease caused by any one of four closely related dengue viruses. Aim of the study was to study radiological features of dengue fever in cases and control. Methods: Randomized, double blind, placebo controlled, parallel group study conducted among 100 seropositive dengue patients,18-60 years of age (fulfilling inclusion and exclusion criteria) at Lala Lajpat Rai hospital, Kanpur for December 2019 October 2021. Selected patients were subjected to history, examination, necessary investigations and then were managed according to national vector borne disease control programme (NVBDCP) guidelines. A total of 100 serology proven dengue patients were included and followed up. Two groups (fifty in each) were allocated by simple first and then systematic random sampling. Case group was given doxycycline and control group was given placebo. Results: USG findings commonly seen in both the cases and control group were hepatomegaly, splenomegaly, ascites right pleural effusion, thickened GB wall and edema. In both the groups, pleural effusion was the most common complication. Conclusions: Ultrasound examinations detected plasma leakage in multiple body compartments around time of defervescence. Presence of plasma leakage in form of ascites and pleural effusion was more in control group as compared to case group seems doxycycline decrease the plasma leakage. Pleural effusion is most common finding of plasma leakage.